Analysis of elementary school teacher needs to learning media android apps based on Smart Apps Creator (SAC) - Aeni, Ani Nur; Hanifah, Nurdinah; Rahimah, Rahimah; Arifuddin, Ahmad; Maulana, Marwan; Akbar, Kamal Aramdan; Hafidz, Achmad Nurul; Al-Faridzi, Muhammad Dzikri Ajri (Universitas Negeri Malang, 2024)
This research is motivated by the fact that learning conditions in the digital era must be supported by digital media, while the use of digital media in learning is still limited due to several obstacles faced by teachers.. The purpose of this study is to analyze the needs of elementary school teachers for SAC-based android application learning media. The research method used a survey with a google form instrument involving 246 elementary school teacher participants from West Java, Central Java and Banten. Data analysis is carried out automatically by google form so that results are obtained in the form of the number and percentage of participants which are visualized in the form of a pie chart and then interpreted into percentage categories and described qualitatively. The results showed that: 1) more than half of the participants already knew the android application learning media, and stated that the android application was appropriate and effective to be used as a learning medium, but less than half of the participants had never made android application media, 2) a small number of participants had known and had seen SAC products, but more than half had the desire to know more about SAC. From these results, it can be concluded that 1) It is necessary to develop a lot of digital learning media such as SAC-based android applications so that they can be used by teachers in teaching, 2) Teachers need to upgrade their knowledge and skills in the use of technology for learning.